Aplikasi E-Commerce Berbasis Web pada PT. Triwarga Dian Sakti - Kevin Giovandi; Arie Kusumawati (UNIVERSITAS KALBIS, 2022)
The system of sales promotion, and marketing at PT Triwarga Dian Sakti is still done manually. This study aims to build a web-based E-Commerce Application at PT Triwarga Dian Sakti in order to facilitate the promotion of the company to attract the attention and desires of customers to buy goods, facilitate customers to obtain information provided by the company, also facilitate the online transaction process, the system built is designed by using a prototyping system development method that covers system analysis using cross-functional diagrams. The system design uses the Unified Modeling Language (UML), system development and programming using the Hypertext Preprocessor (PHP) programming language and the My Structure Query Language (MySQL) database. Testing the system using black-box testing, the results of this study are web-based applications to be able to conduct transactions with price quotes via chat admin and promotional catalogs at PT Triwarga Dian Sakti